PUBG; BETWEEN REAL AND UNREAL - Sihombing, Lambok Hermanto (Jurnal Ilmiah Mandala Education (JIME), 2022)
Playing games is an enjoyable activity. Almost everyone loves it. Player Unknown's Battlegrounds (PUBG) is a game enjoyed by people of all ages, particularly children. Due to its interesting features, PUBG has the potential to become gamers addicted. Furthermore, most of the feature contains violence, which children may imitate. They may believe the content is real. As a result, they will be able to replicate the brutality depicted in the game. They have difficulties determining what is real and unreal. Thus, the author of this scientific study aims to analyse the effect of playing PUBG on youngsters. The dataset was compiled using data from the official PUBG mobile Instagram account @pubgmobile id, the pubgmobile.com website, and articles. Simulacra and Simulation by Jean Baudrillard is applied in this study to aid the author in conducting this analysis. The result of this study indicates that playing PUBG could trigger violence and addiction.